2020
DOI: 10.1002/eji.201848071
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PPE18 protein inhibits MHC class II antigen presentation and B cell response in mice

Abstract: PPE18 protein belongs to PE/PPE family of Mycobacterium tuberculosis. We reported earlier that PPE18 protein provides survival advantage to M. tuberculosis during infection. In the current study, we found that PPE18 inhibits MHC class II‐mediated antigen presentation by macrophages in a dose‐dependent manner without affecting the surface level of MHC class II or co‐stimulatory molecules. PPE18 does not affect antigen uptake or presentation of preprocessed peptide by macrophages. Antigen degradation was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…PPE18 is a crucial virulence factor for the intracellular survival of M. tuberculosis and one of the main components of the M72/AS01E vaccine (31,32). Recently, Komal Dolasia et al reported that PPE18 protein inhibited MHC class II antigen presentation (33). However, we found that two peptides (PPE18 115-129 and PPE18 149-163 ) of PPE18 protein could be recognized and presented by splenolymphocytes from humanized mice.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…PPE18 is a crucial virulence factor for the intracellular survival of M. tuberculosis and one of the main components of the M72/AS01E vaccine (31,32). Recently, Komal Dolasia et al reported that PPE18 protein inhibited MHC class II antigen presentation (33). However, we found that two peptides (PPE18 115-129 and PPE18 149-163 ) of PPE18 protein could be recognized and presented by splenolymphocytes from humanized mice.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, Komal Dolasia et al. reported that PPE18 protein inhibited MHC class II antigen presentation ( 33 ). However, we found that two peptides (PPE18 115-129 and PPE18 149-163 ) of PPE18 protein could be recognized and presented by splenolymphocytes from humanized mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycobacteria inhibit MHC-II synthesis which leads to reduced CD4 + TL-mediated immunity action due to a lack of antigen presentation (Noss et al 2001 ; Dolasia et al 2021 ). Mtb can avoid and/or tolerate phagolysosome formation; this directly affects phagocyte maturation, limits lysosome formation and inhibits phagosome acidification (Wong et al 2013 ; Chen et al 2015 ; Sajid et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%